Crystal structure of N′,2-bis((E)-2-chloro-6-hydroxybenzylidene)hydrazine-1-carbothiohydrazide, C15H12Cl2N4O2S - Liu, Weiping (Zeitschrift für Kristallographie. New crystal structures, 2020)
Cl S, monoclinic, (no. 14), = 12.236(7) Å, = 20.199(10) Å, = 6.992(4) Å, = 105.987(9)°, = 1661.2(16) Å , = 4, ) = 0.0707, ) = 0.1917, = 293(2) K.